Does differentiated instruction affect learning outcome? Systematic review and meta-analysis - Muh. Asriadi AM; Samsul Hadi; Edi Istiyono; Heri Retnawati (Journal of Pedagogical Research, 2023)
In an era of increasingly diverse education, the need to understand the effectiveness of differential instruction on learning outcomes is critical in creating inclusive and student-centered learning experiences. This study aims to comprehensively review the effectiveness of differentiated instruction on student learning outcomes and investigate what moderator variables contribute significantly to the effect of implementing differentiated instruction on student learning outcomes. The study was a systematic review and meta-analysis that utilized 49 primary studies, from which 63 effect sizes were extracted. It was found that there was a significant (gRE = 1.109, p < .01) of the application of differential instruction on student learning outcomes compared to learning in the control group. When measured from the aspect of the measured ability, subjects, grade level, sample size, and index type, there was no significant difference in effect size. However, there was a significant difference in effect size when viewed from the country's perspective.  It was concluded that differential instruction is an appropriate learner strategy used to improve the quality of learning at all levels. However, it is prudent to acknowledge that the effectiveness of implementing differentiated instruction is intrinsically intertwined with the specific context and educational milieu of a given country. This study provides a nuanced understanding that while differentiated instruction holds universal promise, its optimal outcomes are sensitive to contextual influences.